Rapid FEV1 decline and the effects of both FEV1 and FVC on cardiovascular disease: A UK biobank cohort analysis - Jiahui Zhang; Junru Wang; Xiaojun Ma; Yali Wang; Kai Liu; Zhuoyuan Li; Jing Wang; Lisha Na; Jiangping Li (BMC, 2024)
Abstract Background The relationship between lung function and cardiovascular disease (CVD) has emerged as a significant research focus in recent years, but studies on the effects of both forced expiratory volume in 1 second (FEV1) and forced vital capacity (FVC) remain limited. Methods Among 29,662 participants in the UK Biobank study free of CVD, rapid lung function decline was defined as the decline in either FEV1 (greatest quartile), FVC (greatest quartile), or both (when both FEV1 and FVC exceeded the greatest quartile). CVDs include coronary heart disease (CHD), arrhythmias, heart failure (HF), peripheral arterial disease (PAD), and other CVDs (including endocarditis, stroke, and myocardial diseases). Cox proportional hazards models were used to explore the associations between lung function and CVD incidence. Fine‒Gray models were used to account for the competing risk of death. Results Among 29,662 participants in the UK Biobank study free of CVD, the adjusted hazard ratios (HRs) for FEV1 rapid decline were 1.150 (95% CI: 1.009-1.311) for CHD, 1.307 (95% CI: 1.167-1.465) for arrhythmias, 1.406 (95% CI: 1.084-1.822) for HF, 1.287 (95% CI: 1.047-1.582) for PAD, 1.170 (95% CI: 1.022-1.340) for other CVDs, and 1.216 (95% CI: 1.124-1.315) for composite CVD. The adjusted HRs for the impact of both rapid decreases in FEV1 and FVC were 1.386 (95% CI: 1.226-1.567) for arrhythmias, 1.390 (95% CI: 1.041-1.833) for HF, 1.222 (95% CI: 1.054-1.417) for other CVDs, and 1.230 (95% CI: 1.128-1.340) for composite CVD. Conclusions The rapid decline in FEV1 and the impact of both FEV1 and FVC are closely associated with the subsequent incidence of various CVDs and composite CVD.